2014
DOI: 10.1371/journal.pone.0088829
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Hepatitis B Prevalence among Children and Mothers: Results from a Nationwide, Population-Based Survey in Lao People's Democratic Republic

Abstract: BackgroundHepatitis B is regarded as a serious public health issue in Lao People's Democratic Republic (Lao PDR), a Southeast Asian country. However, disease epidemiology among the general population is not well known, and thus a nationwide cross-sectional survey for hepatitis B surface antigen (HBsAg) prevalence in children and their mothers was conducted.Methods and findingsWe applied three-stage cluster sampling using probability proportionate to size. After randomly selecting child (5 to 9 years old) and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 19 publications
3
33
4
Order By: Relevance
“…For sex the result is different from that found in Egypt but the result is similar to that found in Laos. [12] Regarding the environment from Mao et al in Cambodia [13] and in Egypt Iman et al [14] found similar results to ours. We did not find any plausible explanation in the literature for this.…”
Section: Discussionsupporting
confidence: 85%
“…For sex the result is different from that found in Egypt but the result is similar to that found in Laos. [12] Regarding the environment from Mao et al in Cambodia [13] and in Egypt Iman et al [14] found similar results to ours. We did not find any plausible explanation in the literature for this.…”
Section: Discussionsupporting
confidence: 85%
“…Interestingly, large differences are observed when comparing it to the results of two recent surveys conducted in Laos: it is significantly lower than the 8.2% rate reported among 388 pregnant women tested in 2011 in Luang Prabang and Vientiane [2] but significantly higher than the 2.9% rate established in a 2012 nationwide survey conducted on 965 mothers [11]. How can such discrepancies be explained?…”
Section: Discussionmentioning
confidence: 82%
“…This prevalence is in accordance with published studies [7, 8] and unpublished data from the Lao Red Cross that show between 8–10% of adult Lao blood donors nationwide are HBsAg positive. However, it is in contrast to the 2.9% HBsAg positivity in mothers aged 15–49 years in the aforementioned nationwide survey [21]. Regional HBsAg prevalence varies between and within countries, according to vaccination coverage and other factors.…”
Section: Discussionmentioning
confidence: 89%